The Role of the CYP11B2 Promoter Polymorphism in the Diagnosis of Primary Aldosteronism - Żukowski, Łukasz (J Clin Med, 2020)
Background: nowadays, primary aldosteronism (PA) is suggested to be the most frequent cause of secondary hypertension and it reaches 10% of whole hypertensive population. The CYP11B2 promoter polymorphism might cause aldosterone overproduction. The aim of this study was to establish whether the polymorphism CYP11B2 promoter has a significant impact on diagnostic of PA. Material and Methods: study group consisted of 239 hypertensive patients previously diagnosed with adrenal incidentaloma. For diagnose of PA were performed: screening test–aldosterone-renin ratio (ARR) and saline suppression test (SIT) as a confirmatory test. Genotyping was carried out by the real time PCR method. The significance of differences between the groups was evaluated through Student’s t-test. Results: our study revealed that genotype TT had plasma aldosterone concentration (PAC), ARR and SIT significantly higher in comparison with CC patients. The mean PAC in CC was 12.71 ng/dL vs. 20.55 ng/dL in TT patients (p = 0.037), which consequently gave a higher ARR in TT patients (119 vs. 44, p = 0.034). Mean aldosterone concentration in SIT was 2.40 ng/dL in CC patients and 9.99 ng/dL in TT patients (p = 0.046). Patients with CC genotype required less hypotensive drugs in comparison with TT genotype (p = 0.044). PA was recognized in 16 patients. Nine patients had TC genotype, six TT, and one with CC genotype. Conclusion: our study revealed predisposing TT genotype to PA. Additionally, patients with TT genotype, regardless of the PA presence, had more severe hypertension. The determination of the CYP11B2 promoter polymorphism seems to be useful in the diagnosis of PA, especially in cases where it is difficult to properly prepare patients for hormonal tests or even results of the hormonal test are incoherent.